2022
DOI: 10.1177/00031348221096577
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Implications of LGBTQ+ Health Disparities: A Review

Abstract: Lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ+) patients face challenging health care disparities. However, due to restrictions in reporting and collection of sexual orientation and gender identity (SOGI) demographic data, comprehensive studies of surgical disparities in the LGBTQ+ population are limited. This review aims to summarize the existing literature describing surgical disparities in LGBTQ+ patients and to identify areas of surgical care in which further studies are warranted. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Importantly, including SOGIE measures has demonstrated impact in various medical fields. Although its significance is inherently understood in areas like gender-affirming surgery, its value is becoming increasingly recognized in cancer survivorship and other surgical patient outcomes . Given the direct association between gender minority stress and cardiovascular disease, there is a need to understand the social determinants of health in LGBTQ+ adults with cardiovascular disease, which cannot occur without SOGIE data.…”
Section: Importance Of Sexual Orientation and Gender Identity Datamentioning
confidence: 99%
“…Importantly, including SOGIE measures has demonstrated impact in various medical fields. Although its significance is inherently understood in areas like gender-affirming surgery, its value is becoming increasingly recognized in cancer survivorship and other surgical patient outcomes . Given the direct association between gender minority stress and cardiovascular disease, there is a need to understand the social determinants of health in LGBTQ+ adults with cardiovascular disease, which cannot occur without SOGIE data.…”
Section: Importance Of Sexual Orientation and Gender Identity Datamentioning
confidence: 99%
“…Sexual and gender minority populations undergo fewer cancer screening tests compared to non-sexual and gender minority individuals, face challenges in accessing insurance coverage for genderaffirming surgery, experience unique psychosocial risk factors related to surgical care, and in some cases report being refused care because of their identities. [4][5][6] While postoperative outcome data are limited, prior work has raised concern that a patient's sexual and gender minority identity may have clinical implications for surgical care as well. One study of cardiovascular disease in transgender adults found that they had more than 3 times the odds of lifetime venous thromboembolism compared with cisgender individuals.…”
mentioning
confidence: 99%
“…However, we know that disparities in the care provided to these patients exist before they arrive in the operating room. Sexual and gender minority populations undergo fewer cancer screening tests compared to non–sexual and gender minority individuals, face challenges in accessing insurance coverage for gender-affirming surgery, experience unique psychosocial risk factors related to surgical care, and in some cases report being refused care because of their identities . While postoperative outcome data are limited, prior work has raised concern that a patient’s sexual and gender minority identity may have clinical implications for surgical care as well.…”
mentioning
confidence: 99%
“…We read with great interest the work by Adam Awe et al "Surgical Implications of LGBTQ+ Health Disparities: A Review" recently published in the Journal. 1 The Authors highlight with competence and completeness how impactful the treatment of transgender people (TGD) is in surgery. TGD have unique anatomical and pathophysiological characteristics and several specific surgical needs.…”
mentioning
confidence: 99%
“…We read with great interest the work by Adam Awe et al “Surgical Implications of LGBTQ+ Health Disparities: A Review” recently published in the Journal. 1…”
mentioning
confidence: 99%